Sensitivity evaluation of the visual, tactile, and auditory detection response task method while driving. (19th May 2017) - Stojmenova, Kristina; Jakus, Grega; Sodnik, Jaka
ABSTRACT: Objectives : In this article, we evaluate the sensitivity to cognitive load of 3 versions of the Detection Response Task method (DRT), proposed in ISO Draft Standard DIS-17488. Methods : We present a user study with 30 participants in which we compared the sensitivity to cognitive load of visual, audio, and tactile DRT in a simulated driving environment. The amount of cognitive load was manipulated with secondary n -back tasks at 2 levels of difficulty (0-back and 1-back). We also explored whether the DRT method is least sensitive to cognitive load when the stimuli and secondary task are of the same modality. For this purpose, we used 3 forms to present the n -back task stimuli: visual, audio, and tactile. Responses to the task were always vocal. The experiment was based on a between-subject design (the DRT modalities) with 2 levels of within-subject design study (modalities and difficulty of the secondary n -back tasks). The participants' primary task in the study was to drive safely, and a second priority was to answer to DRT stimuli and perform secondary tasks. Results : The results indicate that all 3 versions of the DRT tested were sensitive to detecting the difference in cognitive load between the reference driving period and driving and engaging in the secondary tasks. Only the visual DRT discriminated between the 0-back and 1-back conditions on mean response time. Contrary to expectations, no interaction was observed between DRT modality and the stimuli modality used for presentation of the secondary tasks. Conclusions : None of the 3 methods of presenting DRT stimuli showed a consistent advantage in sensitivity in differentiating multiple levels of cognitive load if all response times, hit rates, and secondary task performance are considered. If only response time is considered, the visual presentation of the DRT stimulus used in this study showed some advantages. In interpreting these data, it should be noted that the methods of DRT stimulus presentation varied somewhat from the currently proposed draft ISO standard and it is possible that the relative salience level of the visual DRT stimulus influenced the findings. It is further suggested that more than 2 levels of difficulty of the n -back task should be considered for further investigation of the relative sensitivity of different DRT stimuli modalities. Parameters that indicate change in cognitive load (response time, hit rate, task performance) should be analyzed together in assessing the overall impact on the driver and not individually, in order to obtain a fuller insight of the assessed cognitive load.